Del bazar a la familia: una aproximación crítica a las “idealizaciones” políticas rortyanas - Mattio, Eduardo (2008)
“From the Bazaar to the Family: A Critical Approach to Rortyan Political ‘Idealizations’”. Richard Rorty’s political work has united, in a unique narrative, the social hopes of liberal egalitariasm with the philosophical anti-essentialism of postmodernism. As a consequence, when Rorty’s political philosophy “justifies” the institutions of liberal democracy it does not appeal to metaphysical or transcendent fundamentals firmly established; however, it does appeal to idealizations, to narrative constructions that allow emphasizing those componentsof our political practices that we think are worthy and minimize those that we think are secondary. This article analyzes two of the idealizations used by Rorty to summarize the purposes of his liberal democracy: Kuwaiti bazaar -images of the separation between public and private sphere- and of the family -archetype of the relations that should be promoted in liberal societies. These narratives resources not only express the nature of his political project but also show the limitations at the moment of realizing his main objective: the expansion of solidarity.